System Center Virtual Machine Manager 2022: Enhanced Cloud Integration and Management Capabilities - Somaning Turwale, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
System Center Virtual Machine Manager (SCVMM) 2022 represents a transformative advancement in private cloud management, offering enhanced capabilities across virtualization, deployment, and cloud integration domains. This comprehensive platform introduces sophisticated hardware-level security protocols, dynamic resource allocation mechanisms, and intelligent orchestration capabilities that significantly improve operational efficiency. The integration with Azure Arc and support for Azure Kubernetes Service demonstrates SCVMM's evolution in hybrid cloud management, while enhanced data protection solutions ensure robust security and recovery capabilities. The platform's implementation of energy-aware management protocols and low-carbon operational methodologies showcases Microsoft's commitment to environmental sustainability without compromising performance. Through advanced predictive analytics, automated workflow management, and streamlined deployment architectures, SCVMM 2022 addresses the growing demands of modern enterprise environments. This article examines the platform's core enhancements, deployment methodologies, cloud integration capabilities, and impact on enterprise operations while providing implementation best practices derived from extensive research and real-world deployments.
Keywords: Cloud Management; Virtualization; Azure Integration; Enterprise Infrastructure; Sustainable Computing